Cross-Cultural Connections in Crime Fictions
XI, 180 p.
Keywords: A collection of ten original essays forging new interdisciplinary connections between crime fiction and film, encompassing British, Swedish, American and Canadian contexts. The authors explore representations of race, gender, sexuality and memory, and challenge traditional categorisations of academic and professional crime writing.